The significance of EIA and DPR in the development process - From the developer viewpoint - Othman, Asiah (2002)
There are various rules and procedures that need to be complied with before any approvals could be granted. In housing development developers are needed to prepare Development Proposal (DPR) Reports and in some cases they are required to prepare the Environmental Impact Assessment (EIA) Report as well. Those two reports has its significance as a mechanism or tools used by the approval authority in controlling and monitoring the development that are taking place. This could ensure a proper development that could minimise any adverse impact on the surrounding and the environment. Nevertheless, such requirement will have some implication towards the developers who are now needed to prepare at their own cost. Definitely this will have some repercussion towards their business undertaking. Thus, this paper attempts to look into the significance of the reports in the development process with particular emphasis on to the developers.